Tanzanian midwives' perception of their professional role and implications for continuing professional development education - Jones, B.; Michael, R.; Butt, J.; Hauck, Yvonne (2015)
© 2015 Elsevier Ltd. This study explored Tanzanian midwives' perceptions of their professional role within their local context. Findings were to inform recommendations for continuing professional development education programs by Western midwifery educators. Using focus group interviews with sixteen Tanzanian midwives, the findings revealed that the midwives' overwhelming focus was on saving lives of women and newborns. The fundamental elements of saving lives involved prioritising care through receiving handover and undertaking physical assessment. Midwives were challenged by the poor working conditions, perceived lack of knowledge and associated low status within the local community. Based upon these findings, recommendations for continuing professional development education for Tanzanian midwives must ensure that saving lives is a major focus and that strategies taught must be relevant to the low-resource context of this developing country. In recognition of the high-risk women being cared for, there needs to be a focus on the prevention and management of maternity emergencies, in collaboration with medical practitioners.